1993
DOI: 10.1083/jcb.121.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Integrin beta 1- and beta 3-mediated endothelial cell migration is triggered through distinct signaling mechanisms.

Abstract: Abstract. Human umbilical vein endothelial cell attachment, spreading and migration on collagen and vitronectin are mediated by integrins ot~t and etv/33, respectively, and these events take place in the absence of cytokines, growth factors, or chemoattractants. Cell attachment and spreading on these ligands occur in the absence of extracellular calcium, as does migration on collagen. In contrast, vitronectin-mediated migration is absolutely dependent on the presence of extracellular calcium. Cell contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
1
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(196 citation statements)
references
References 46 publications
5
188
1
2
Order By: Relevance
“…Together, these observations all point to a role of kindlin-2 in regulating ␣V␤3 activation. The pivotal role of kindlin-2-dependent ␤3 integrin activation in angiogenesis is consistent with extensive evidence demonstrating the importance of ␣V␤3 in angiogenesis (reviewed in Avraamides et al 5 ) using Abs, peptides, small molecules, or antisense approaches in vitro 33,34 and in vivo. 4,35 Angiogenesis induced by growth factors or tumors is also suppressed in knock-in mice expressing Y747F/Y759F mutations in the ␤3 cytoplasmic tail of ␣V␤3.…”
Section: Discussionsupporting
confidence: 51%
“…Together, these observations all point to a role of kindlin-2 in regulating ␣V␤3 activation. The pivotal role of kindlin-2-dependent ␤3 integrin activation in angiogenesis is consistent with extensive evidence demonstrating the importance of ␣V␤3 in angiogenesis (reviewed in Avraamides et al 5 ) using Abs, peptides, small molecules, or antisense approaches in vitro 33,34 and in vivo. 4,35 Angiogenesis induced by growth factors or tumors is also suppressed in knock-in mice expressing Y747F/Y759F mutations in the ␤3 cytoplasmic tail of ␣V␤3.…”
Section: Discussionsupporting
confidence: 51%
“…Recent work in our laboratory revealed that ETS-1 converts EC to an invasive phenotype by inducing the expression of proteases including u-PA, MMP-1, MMP-3, and MMP-9, as well as integrin β3 subunit as target genes in ECs. 11,31) u-PA, MMP-1, MMP-3, and MMP-9 are responsible for degradation of extracellular matrices, whereas u-PA 32,33) and integrin β3 34,35) are responsible for cell migration. Therefore, the inhibitory effect of PD98059 on cell migration may derive at least in part from the impaired expression of ETS-1 target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Mediates endothelial cell attachment, spreading, and migration 419 Inhibits endothelial cell apoptosis 199 Highly expressed on activated endothelial cells 420,421 Present on angiogenic capillary sprouts 197,198 Localizes MMP-2 to capillary sprouts 198 Required for FGF-stimulated angiogenesis in vivo 195,196 α v β 5 Required for VEGF-stimulated angiogenesis in vivo 195,196 MMPs…”
Section: Ecm Extracellular Matrixmentioning
confidence: 99%